1981
DOI: 10.1044/jshr.2404.557
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Tympanometric Estimates of Ear Canal Volume

Abstract: The accuracy of tympanometric estimates of ear canal volume was evaluated by testing the following two assumptions on which the procedure is based: (a) ear canal volume does not change when ear canal pressure is varied, and (b) an ear canal pressure of 200 daPa drives the impedance of the middle ear transmission system to infinity so the immittance measured at 200 daPa can be attributed to the ear canal volume alone. The first assumption was tested by measuring the changes in ear canal volune in eight normal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 0 publications
3
52
0
2
Order By: Relevance
“…For frequencies up to about 1 kHz, the adult ear canal can be modeled as a lumped acoustical element ͑e.g., Shanks and Lilly, 1981͒. This assumption is valid up to higher frequencies in the newborn canal because it is smaller than the adult canal.…”
Section: Tympanometrymentioning
confidence: 95%
See 2 more Smart Citations
“…For frequencies up to about 1 kHz, the adult ear canal can be modeled as a lumped acoustical element ͑e.g., Shanks and Lilly, 1981͒. This assumption is valid up to higher frequencies in the newborn canal because it is smaller than the adult canal.…”
Section: Tympanometrymentioning
confidence: 95%
“…Subtracting these values from the average equivalent-volume change of 157 mm 3 yields predicted volume changes caused by tympanic-membrane displacement of about 56, 104, and 120 mm 3 , respectively. No independent measurements of newborn tympanic-membrane volume displacements are available for comparison, and measurements in adult ears ͑e.g., Shanks and Lilly, 1981;Dirckx and Decraemer, 1992; Gaihede, 1999͒ may be quite different.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insert earphones were not used because our previous work has shown that TM perforations can affect the ear canal sound pressure generated by insert earphones such that the measured hearing loss is substantially larger than the actual loss (7). Tympanometry is an established method of measuring the volume contained within a closed air space (8)(9)(10)(11). The tympanogram read-out in an ear with a TM perforation is an estimate of the combined volume within the ear canal, middle-ear, and mastoid.…”
Section: Protocol For Data Collectionmentioning
confidence: 99%
“…Clinically, these pressure values range from +200 to -400 daPa. According to Shanks and Lilly [1], the most accurate measurements are those in the low pressure end.…”
Section: Introduction To Tympanometrymentioning
confidence: 99%